105 Blood quest – preparing children for blood tests: using arts-based techniques in creative research and app development. (4th October 2017) - Gibson, F; Hall, S; Oulton, K; Wray, J
Abstract : Background: The Blood Quest app is an interactive digital tool built on the outcomes of a collaborative research study led by the Centre for Outcomes and Experience Research in Children's Health, Illness and Disability (ORCHID) and the GOSH Arts programme. It aims to prepare children for blood tests by helping them to find out about blood and what happens during a blood test. It was developed in conjunction with patients and designed to be fun and informative. Blood tests are one of the most feared procedures by children and young people, and research shows that preparation, education and distraction can all be effective in helping them cope with stressful procedures and anxiety whilst in hospital. Project: Patients, artists, designers and researchers worked together to develop the app, with the aim of creating a 'tool' that helps inform, and distract children and young people whilst having a blood test. The app includes information about blood and venepuncture, fun animal heart facts, quizzes and a specifically developed distraction game that is designed to be played during the test. Blood Quest was created for the ipad platform and can be downloaded free from the Apple and GOSH app stores. Evaluation Methodology: Mixed methods evaluation pre and post launch aiming to assess; Feasibility and acceptability of the app from a parent perspective Impact of app on patient experience This presentation will focus on the background and development of the project and our evaluation of the app so far. We will look at limitations of the study, suggestions for further development and lessons learnt for other departments thinking of embarking on app creation. Blood Quest has been generously funded by Roald Dahl's Marvellous Children's Charity, Burdett Trust for Nursing and Great Ormond Street Hospital Children's Charity.